Temporal consistency of behavior trait measurements in guide dogs - Hilby, Emma K.; Rendahl, Aaron; Russenberger, Jane; Zimmermann, Madeline; Mickelson, James R.; McCue, Molly E. (Frontiers in Veterinary Science, 2025)
Guide dog organizations have strict criteria to breed, raise, and select dogs to assist people with visual impairments. In collaboration with Dr. James Serpell, several guide dog training organizations developed a scoring tool called the Behavior Checklist (BCL) to evaluate candidate guide dogs. The tool’s use has expanded to the entire assistance dog industry and is rapidly emerging as the standard behavior assessment. Since 2003, Guiding Eyes for the Blind (GEB) has used the BCL to measure individual dogs’ behaviors up to 8 times between puppyhood and final placement. Here, we evaluate the consistency of the BCL over multiple evaluations in a population of 3,969 Labrador Retrievers raised by Guiding Eyes. We grouped BCL evaluations by two methods, factor analysis, and trainer-defined groups, and summarized groupings of behavior in two ways, using mean and lowest scores. We then determined the agreement between pairs of evaluations using kappa statistics and the predictive capacity of early BCL scores to predict later scores using positive and negative predictive values. Evaluations that are similar in nature and those that are scored within 3 to 6 months of one another agree the most. When a dog scores well early in life, they are likely to consistently score well and the dog’s behavior is unlikely to regress over time. We also found that dogs who score poorly early in life either improve their scores on later evaluations with training intervention or are removed from training. One limitation of this data is that dogs who score poorly at early time points are often removed from training and the data from later BCL evaluations is biased toward higher-scoring dogs. Regardless, these data show that the BCL is an effective way to evaluate assistance dog behavior and has some predictive capacity.